2023
DOI: 10.7759/cureus.35957
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Assessment of Bilateral Asymmetry in the Upper Extremities of Living Humans

Abstract: Objective Injuries resulting from trauma or tumor resection may cause length alterations in the bones of the upper extremities (UE) requiring reconstruction. Direct contralateral bone is often used to determine the appropriate length for reconstruction but fails to account for potential asymmetry. Given the paucity of data assessing asymmetry in living populations and the need for accurate length approximation, we developed a study evaluating UE long bone asymmetry using radiographic imaging in livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have reported on side‐to‐side differences in the morphology of proximal femur, distal femur, and other long bones of the body [8, 17, 25]. Such studies can help to determine if contralateral side can be used for screening or templating purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported on side‐to‐side differences in the morphology of proximal femur, distal femur, and other long bones of the body [8, 17, 25]. Such studies can help to determine if contralateral side can be used for screening or templating purposes.…”
Section: Discussionmentioning
confidence: 99%